Ecotoxicology and human health risk assessment of heavy metal in tiny scale barb [Thynnichthys thynnoides (Bleeker, 1852)] from upstream Perak River, Malaysia - Ahmad Affandi, Farhana (2020)
The upstream of Perak River has continuously received pollution from anthropogenic activities. These activities are responsible for the release of heavy metals into the environment. Thus, this study aimed to profile the concentrations of heavy metals in water, sediment, and tiny scale barb Thynnichthys thynnoides of the upstream of Perak River by integrating analytical and statistical approaches. This study also assessed the potential ecological and human health risks to heavy metals contamination. Furthermore, this study investigated the effect of heavy metal contamination on genetic variation of the tiny scale barb populations of this river using microsatellite loci from cross-species amplification. The concentrations of heavy metals [i.e. aluminum (Al), arsenic (As), copper (Cu), iron (Fe), manganese (Mn), lead (Pb), and nickel (Ni)] were analysed by the inductively coupled plasma mass spectrometry (ICP-MS). The results revealed that the water and sediment of this river were primarily polluted by As and potentially by Cu and Pb. The mean concentrations of As in both water (0.17 mg/L) and sediment (878.6 mg/kg) were observed to exceed the standard quality guidelines recommended for water (0.01 mg/L, Ministry of Health Malaysia) and sediment (70 mg/kg, Hong Kong Environmental Protection Department), respectively. The principal component analysis (PCA) then identified mixed anthropogenic sources related to the pollution mainly from mining, followed by logging and plantation activities. The high bioaccumulations of As in the tiny scale barb tissues were also correlated to the high concentrations of As in the river. The contamination factor (CF) and potential ecological risk index (RI) showed that this Perak River is severely contaminated by As and could pose a serious ecological risk to aquatic organisms. The concentration of As in the muscle tissues of tiny scale barb (1.00 mg/kg) has reached the maximum permissible limit by the Malaysian Food Regulations (1.00 mg/kg) and target hazard quotient (THQ) suggested that daily consumption of this fish would likely to cause adverse health effects to the consumer. Despite the high levels of metals in the tiny scale barb tissues, it shows no correlation with genetic variation in the tiny scale barb populations. However, this study observed reduced genetic diversity in tiny scale barb populations above the Kenering dam compared to the populations below dam. This is an indication of genetic divergence and inbreeding due to the physical river barrier. Recent population bottlenecks were also observed in the populations above the dam possibly due to the effects of pollution and overfishing. In conclusion, this study has successfully provided data on heavy metals in river ecosystems for the purpose of monitoring, environmental protection and human safety. This study has also provided valuable genetic information for the fisheries sector and native species conservation efforts.